Possible Economic Outcomes of a Trade Agreement with the European Union - Alexander Knobel; Bekhan Chokaev (Gaidar Institute for Economic Policy, 2014)
This paper investigates the possible economic effects of Russia-EU free trade agreement, implying a mutual zero import tariffs in the trade of the Customs Union and the EU. Analysis of the effects is made using CGE Globe v1 model. We estimate the impact of an FTA on the economies, both at the level of the entire economy and at the industry level. The sensitivity analysis is made. It is shown that, in both relative and absolute terms, Russia potentially more benefits from the agree-ment than the EU. The cumulative gain of the CU is strictly positive, but the benefits and costs are unevenly distributed among its members, with negative effect for Belarus.
Keywords: C68; F15; F17; 330; Customs Union; European Union; Free Trade Agreement; CGE